Atrial myofibroblast activation and connective tissue formation in a porcine model of atrial fibrillation and reduced left ventricular function - Lugenbiel, Patrick; Wenz, Fabian; Govorov, Katharina; Syren, Pascal; Katus, Hugo; Thomas, Dierk (Life sciences, 2017)
Aims: Atrial fibrillation (AF) is associated with fibrosis that slows electrical conduction and causes perpetuation of the arrhythmia. The molecular characterization of AF pathophysiology may provide novel therapeutic options. This study was designed to elucidate profibrotic signaling and myofibroblast activation in a porcine model of atrial tachypacing-induced AF and reduced left ventricular function. Materials and methods: Ten domestic pigs were randomized to sinus rhythm (SR) or AF groups. Prior to AF induction and on day 14 the animals underwent echocardiographic examinations. Profibrotic pathways were analyzed in right atrial tissue obtained from AF animals compared to SR controls using histology, immunofluorescence microscopy, Western blot, and real-time PCR. Key findings: AF was associated with atrial dilation, increased atrial fibrosis, and enhanced expression of collagens I and V in right atrial tissue after 14days follow-up. The fraction of α-smooth muscle actin (SMA)-producing activated myofibroblasts was elevated in AF, whereas the abundance of vimentin-expressing inactive fibroblasts was not affected. Profibrotic signaling involved upregulation of TGF-β1, Smad2/3, and CTGF. Significance: The transformation of atrial fibroblasts into myofibroblasts through activation of TGF-β1 and CTGF emerged as potential cellular trigger of fibrogenesis. Prevention of fibroblast-to-myofibroblast switching may serve as target for remodeling-based antiarrhythmic AF therapy.